Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Section 7.4 - Adding, Subtracting, and Dividing Radical Expressions - Exercise Set: 15

Answer

$6\sqrt{2x}$

Work Step by Step

Simplify each radical to obtain: $=3\sqrt{16(2x)} - 2\sqrt{9(2x)} \\=3\sqrt{4^2(2x)} -2\sqrt{3^2(2x)} \\=3(4)\sqrt{2x}- 2(3)\sqrt{2x} \\=12\sqrt{2x} - 6\sqrt{2x}$ RECALL: The distributive property states that for any real numbers a, b, and c: (1) $ac + bc = (a+b)c$ (2) $ac-bc=(a-b)c$ Use rule (2) above to combine like terms and obtain: $=(12-6)\sqrt{2x} \\=6\sqrt{2x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.